2013 IEEE Wireless Communications and Networking Conference (WCNC) 2013
DOI: 10.1109/wcnc.2013.6555268
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of voltage- and clock-scaling-induced timing errors in stochastic LDPC decoders

Abstract: Abstract-Low Density Parity Check (LDPC) decoders have an inherent capability of correcting the transmission errors that occur, when communicating over a hostile wireless channel. This capability allows LDPC-coded schemes to employ lower transmission energies than uncoded schemes, at the cost of introducing a significant processing energy consumption during LDPC decoding. Traditional energy-reduction techniques, such as voltage and clock scaling can be employed for reducing the LDPC decoder's energy consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Timing errors in the context of the stochastic decoders have been considered recently by Perez-Andrade et al [11] who have shown an inherent tolerance to timing errors of these type of decoders. While the error injection at transistor level was thoroughly analyzed, the decoder data-dependence was not considered.…”
mentioning
confidence: 99%
“…Timing errors in the context of the stochastic decoders have been considered recently by Perez-Andrade et al [11] who have shown an inherent tolerance to timing errors of these type of decoders. While the error injection at transistor level was thoroughly analyzed, the decoder data-dependence was not considered.…”
mentioning
confidence: 99%